O processo de recall na indústria automobilística: caracterização, análise e indicadores de desempenho do mercado brasileiro - Silva, Ivan Luiz Laranjeiras (2011)
The Brazilian automotive industry has been prominent in the international arena, being among the largest producers of cars, buses and trucks. All this automotive production volume, seeking to meet the demand of the market is susceptible to variability in product quality, and this fact is aggravated when it extrapolate the internal barriers from the manufacturer. When this defect is harmful or dangerous, and undermines the health and safety of the user, the product manufacturer has the responsibility to collect and repair the defect, procedure commonly known as Recall. This study aimed to describe, conceptualize, analyze and verify the main issues in the process of Recall in the Brazilian market during the period of 2000 to 2010, analyzing it both as a single variable, and as its interaction with other variables. A exploratory research was conducted, with data collection in public sources, which provided the sample for analysis. The study results showed that the domestic automotive industry performs less Recalls compared to other countries, showed that part of the demand was negatively affected after the announcement of a Recall, and that there is not a significant interaction of Recall with other related variables.